2014
DOI: 10.3390/nu6093641
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Concentrations in Adults with HIV/AIDS on Highly Active Antiretroviral Therapy

Abstract: HIV/AIDS patients are probably more predisposed to vitamin E deficiency, considering that they are more exposed to oxidative stress. Additionally, there are an extensive number of drugs in the highly active antiretroviral therapy (HAART) regimens that may interfere with vitamin E concentrations. The objective of this study was to compare serum concentrations of alpha-tocopherol in 182 HIV/AIDS patients receiving different HAART regimens. The patients were divided into three groups according to regimen: nucleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
8
1
1
Order By: Relevance
“…Another study by Kaio et al [8] compared α -tocopherol levels with antiretroviral classes and showed a decrease of this vitamin in nearly 20% of PLWHA [8]. Conversely in our study approximately 60% and 90% of the PLWHA showed α -tocopherol deficiency before and after cART introduction, respectively (data not shown).…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Another study by Kaio et al [8] compared α -tocopherol levels with antiretroviral classes and showed a decrease of this vitamin in nearly 20% of PLWHA [8]. Conversely in our study approximately 60% and 90% of the PLWHA showed α -tocopherol deficiency before and after cART introduction, respectively (data not shown).…”
Section: Discussioncontrasting
confidence: 63%
“…After cART we observed a reduction in lutein ( p = 0.018) and lycopene levels ( p = 0.019) only in G2 group and in β -carotene ( p < 0.010) and α -tocopherol ( p < 0.050) in both G1 and G2 (Table 2). We also categorized the results of vitamins considering reference values previously established by Kaio et al [8] (<1.0 for β -carotene, <0.7  μ mol/L for retinol and <16.0  μ mol/L for α -tocopherol). The percentages of individuals with values below the ideal, prior to therapeutic initiation, were 93%, 17%, and 60% for β -carotene, retinol, and α -tocopherol, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P = 0,01 p = 0,02 p = 0,02 p = 0,01 p = 0,01 P = 0,01 p = 0,01 p = 0,03 p = 0,05 p = 0,01 p = 0,01 p = 0,01 p = 0,01 POTULAR et al, 2006;LEHNERT et al, 2014). O estado nutricional dos indivíduos da amostra é semelhante a outros estudos (FLORINDO et al, 2007;KAIO, 2013). A melhoria das condições de saúde de PVHIV/aids, em decorrência da TARV, reflete também no maior número de indivíduos eutróficos.…”
Section: Caracterização Dos Indivíduos Do Ensaio Clínico De Acordo Counclassified